(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
As of now, Indian labour law reform is a hot-button issue in the country. We’re all aware thatlabour regulations in India now impose rigidity on the country’s economy, which has an adverse effect onour progress. Despite the fact that Indian labour rules are extensive, complicated and often confusing,they encourage litigation rather than resolving industrial relations difficulties. A number of unions haveprotested against proposed changes to labour and industrial regulations, claiming that they weredeveloped without their input and that the changes favor companies over workers. The government arguesthe changes are necessary for the growth of our country. As a result, this study looks at the sluggish paceof changes in India’s workforce and their impact on the economy as a whole. Policy gridlock on labourreforms has prevented the nation from reaping demographic benefits. In terms of luring internationalinvestors or enticing local businesses to build industrial facilities, irregular changes in labour rules havebeen mostly ineffective. The paper covers the current government’s efforts to implement labour reformsin India, as well as the need for such changes in the country.